Skate! : your guide to inline, aggressive, vert, street, roller hockey, speed skating, dance, fitness training, and more - Shafran, Michael (Extreme sports (Washington, D.C.), 2003)
Provides instruction in everything from standing on skates for the first time to dancing or exercising on them.